Adaptations made to delivery of comprehensive medication management in the community pharmacy setting during COVID-19 - Morgan K. Stoa; Caitlin K. Frail; Joel F. Farley; Deborah L. Pestka; Carrie M. Blanchard (Elsevier, 2021)
Background: As a result of COVID-19, numerous adaptations were made to health care delivery, including comprehensive medication management (CMM) delivered in community pharmacies. Objective: Identify and describe the adaptations that have been made to the delivery of CMM among community pharmacies due to COVID-19. Methods: Community pharmacies participating in a CMM implementation and research initiative had regular coaching calls throughout COVID-19 and completed a survey of changes that occurred as a result of COVID-19. Coaching notes and survey results were summarized and mapped to the Framework for Reporting Adaptations and Modifications-Enhanced (FRAME) to systematically capture changes that occurred. Results: A number of reactive adaptations were made to CMM delivery as a result of COVID-19, including increased virtual or remote delivery of CMM, delaying CMM visits to allow pharmacies to provide care directly related to the pandemic including COVID-19 testing and vaccines, wearing personal protective equipment (PPE) in visits, new ways of obtaining clinical patient information, and shifting CMM staffing models. Conclusion: Adaptations that occurred to CMM during COVID-19 allowed pharmacists to continue to serve their patients and meet public health needs.